Unveiling the First Neobatrachian (Anura) Discovered in the paleokarst system of Bolt’s Farm (Plio-Pleistocene; Cradle of Humankind), South Africa - (:unkn) unknown (My University, 2024)
Anurans are widely diversified in South Africa, with more than 150 recognised species across the country. However, most the known fossil records of anurans are concentrated in the southern part of South Africa, within the rich Pliocene site of Langebaanweg. Isolated anuran elements have been recovered in the Pliocene deposits of the Cradle of Humankind, but none from the multi-localities site of Bolt’s Farm (Plio-Pleistocene). A small block containing an articulated anuran specimen was recently discovered from the Milo A site from Bolt’s Farm. We analysed this specimen using CT-scanning to describe its osteology. Surprisingly, the cavity housing the skeleton took the shape of the body of the individual, revealing a small sized individual with a triangular-shaped head. The preserved skeletal elements (around 50% of the skeleton) shows clear synapomorphies of the Ranoidea. A comparison between our specimen and members of all South African ranoid families allow us to highlight numerous osteological similarities between our specimen and taxa of the Pyxicephalidae, leading to a putative attribution to this large African family. In addition, the position of the body is identical to the position of a dormant pyxicephalid, suggesting that our specimen died during a dormancy period, in the dry season. This supports the current paleoenvironment reconstruction, an open savannah with marked seasonality
Keywords: African Research